2017
DOI: 10.1371/journal.pone.0174872
|View full text |Cite
|
Sign up to set email alerts
|

Does Tai Chi relieve fatigue? A systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundFatigue is not only a familiar symptom in our daily lives, but also a common ailment that affects all of our bodily systems. Several randomized controlled trials (RCTs) have proven Tai Chi to be beneficial for patients suffering from fatigue, however conclusive evidence is still lacking. A systematic review and meta-analysis was performed on all RCTs reporting the effects of Tai Chi for fatigue.MethodsIn the end of April 2016, seven electronic databases were searched for RCTs involving Tai Chi for fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
2
30
0
3
Order By: Relevance
“…Tai chi (TC) may be one such clinical intervention that directly addresses both vitality and mood symptoms in MDD. Originating from China, TC is a mind-body contemplative exercise that facilitates the sense of vitality (i.e., qi or vital energy flow in the body) by incorporating awareness of posture; slow, focused, and low-impact movements; and deep breathing to improve underlying physiological and psychological imbalances (Wolf et al, 1997;Sandlund, 2000;Xiang et al, 2017). Previous studies have documented TC's clinical efficacy in improving both the subjective sense of vitality as well as mood in a wide variety of clinical populations, including rheumatism (Uhlig et al, 2010), heart failure (Yeh et al, 2016), multiple sclerosis (Burschka et al, 2014), and cancer (Zeng et al, 2014) as well as in risk of falling (Del-Pino-Casado et al, 2016), Parkinson's disease, cognitive impairment and dementia, stroke, and chronic obstructive pulmonary disease (Huston and McFarlane, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Tai chi (TC) may be one such clinical intervention that directly addresses both vitality and mood symptoms in MDD. Originating from China, TC is a mind-body contemplative exercise that facilitates the sense of vitality (i.e., qi or vital energy flow in the body) by incorporating awareness of posture; slow, focused, and low-impact movements; and deep breathing to improve underlying physiological and psychological imbalances (Wolf et al, 1997;Sandlund, 2000;Xiang et al, 2017). Previous studies have documented TC's clinical efficacy in improving both the subjective sense of vitality as well as mood in a wide variety of clinical populations, including rheumatism (Uhlig et al, 2010), heart failure (Yeh et al, 2016), multiple sclerosis (Burschka et al, 2014), and cancer (Zeng et al, 2014) as well as in risk of falling (Del-Pino-Casado et al, 2016), Parkinson's disease, cognitive impairment and dementia, stroke, and chronic obstructive pulmonary disease (Huston and McFarlane, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We identified one recent systematic review and meta-analysis that synthesized the evidence from all RCTs that have examined the effects of Tai Chi on fatigue as a specific primary outcome (Table 2). 15 From ten RCTS and 689 participants, which included individuals with specific health conditions such as lung/breast cancer, multiple sclerosis, rheumatoid arthritis, chronic obstructive pulmonary disease, and age-related fatigue, Tai Chi interventions that ranged in duration from 4 to 24 weeks improved fatigue more than control interventions that included stretching, low impact exercise, health education and conventional nursing (SMD: -0.45, 95% confidence interval (CI): -0.70, -0.20).…”
Section: Resultsmentioning
confidence: 99%
“…It is beneficial to both physical and psychological health (Chen et al., ; Jahnke, Larkey, Rogers, Etnier, & Lin, ). Previous studies have also shown that qigong may reduce cancer‐related fatigue; however, the evidence is moderate, and potential biases exist (Xiang, Lu, Chen, & Wen, ; Zeng, Luo, Xie, Huang, & Cheng, ).…”
Section: Discussionmentioning
confidence: 99%